Uniformização da jurisprudência no Direito Processual Civil Brasileiro - Muszkat, André (2018)
This work aims to analyze the methods of case law standardization existing in the Brazilian Civil Procedure Law, by putting into context the law, its evolution and comparing the common law and the civil law systems. It is notorious that the search for expeditious solutions before the Judiciary Branch, as well as greater legal certainty to judicial demands – particularly those dealing with the same object –, is continuous and was broadly discussed since the effectiveness of the Civil Procedure Code of 2015. In order to do so, we will trace an evolutionary overview of the standardization case law methods as from the first Brazilian encodings, detailing the current methods established in the Civil Procedure Code. Besides, we will conceptualize case law and the evolution of its use until current days, under the guiding principles of Civil Procedure. We will also delineate a parallel between the civil law (Brazilian) and common law systematics, highlighting common and differentiation aspects as to the use of case law standardization in each of the systematics. We will pursue, moreover, to dwell on the apparent conflict between the standardization of the case law and the legal certainty it represents and the judge’s discretion